Analisis Isi Pesan Dakwah Dalam Film Insya Allah Sah Karya Benni Setiawan - Rijal Nur Amali; Tengku Walisyah (Fakultas Agama Islam Universitas Billfath, 2024)
This research aims to ascertain the significance of the Islamic ethical message conveyed in the film